KINERJA PRODUKSI DAN KEBERLANJUTAN AGROINDUSTRI EMPING MELINJO DI KECAMATAN TAKTAKAN KOTA SERANG - Shelma Anantapuri; Adia Nugraha; Wuryaningsih Dwi Sayekti (Lampung University, 2021)
This research aimed to analyze procurement of raw materials, production perfomance, fixing cost of goods sold, application of marketing mix, and the sustainability of emping melinjo agroindustry. The location of this research was chosen purposively in Taktakan Subdistrict Serang City in which samples were all of three emping melinjo Agroindustries. The data of this research was primary and secondary data that was collected in March – April 2019. The methods of data analysis used in this research were descriptive, qualitative and quantitative analyses. The results of this research showed that procurement of melinjo raw materials had not appropriate with the six right criteria which were right on time, place, quality, quantity, type, and price. Production performance of emping melinjo agroindustry was quite good although the flexibility component had not been fulfilled yet. Fixing cost of goods sold of emping melinjo agroindustry had been profitable. Application of marketing mix had been implemented quite well although it needs to be improved in several aspects such as promotion. The sustainability of emping melinjo agroindustry in Taktakan Subdistrict Serang City has a good prospect. Key words: agroindustry, emping melinjo, perfomance, sustainability